High cell density fermentation of Candida rugosa on palm oil for lipase production and its mass transfer investigation / Mohd Nur Ikhmal bin Salehmin - Salehmin, Mohd Nur Ikhmal (2014)
Extracellular lipase of the yeast Candida rugosa was produced via high cell density fed-batch fermentations using palm oil as the sole source of carbon and energy. Feeding strategies consisted of a pH-stat operation, foaming-dependent control and specific growth rate control in different experiments. Compared to foaming-dependent feeding and the pHstat operation, the specific growth rate control of feeding proved to be the most successful. At the specific growth rate control set point of 0.05 h1, the final lipase activity in the culture broth was the highest at 700 U L1. This was 2.6-fold higher than the final enzyme activity obtained at a specific growth rate control set point of 0.15 h1. The peak enzyme concentration achieved using the best foaming-dependent control of feeding was around 28% of the peak activity attained using the specific growth rate control of feeding at 0.05 h1. Similarly, the peak enzyme concentration attained using the pH-stat feeding operations was a mere 9% of the peak activity attained by specific growth rate control of feeding at a setpoint of 0.05 h1. The highest biomass specific productivity of the enzyme was 0.19 U g1 h1 for the fed-batch operation with the specific growth rate controlled at 0.05 h1. Fedbatch fermentations were performed in a 2-L stirred-tank bioreactor (30 C, pH 7) with the dissolved oxygen level controlled at 30% of air saturation. Investigation on gas-liquid and liquid-liquid mass transfers by experimental and theoretical means was also carried out. The investigation was simulated in xanthan gum solution which resembles the viscosity of High Cell Density Fermentation (HCDF) at 1.68 mPa.s. Established correlations were successfully used to predict kLa value at different agitation rate ranging from 200-800 rpm for both oil and oxygen mass transfers under HCDF condition. However, the correlations failed to predict kLa value at the highest agitation rate used (1000 rpm) for liquid-liquid mass transfer.